HUBUNGAN KELENTURAN PERGELANGAN TANGAN DAN EXSPLOSIVE POWER DENGAN HASIL TOLAK PELURU PADA SISWA PUTRA KELAS IX SMPN 1 ROKAN IV KOTO UNIVERSITAS RIAU - Sabri, Rahmat; ', Ramadi; ', Yuherdi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problems in this study originated from the observation that the author is in the field that researchers found deficiencies at the time of repulsion is still a lack of flexibility of the wrist and the explosive force at the time rejected profits resulting are less than the maximum repulsion. The purpose of this research was to determine the relation wrist flexibility and explosive power with the results of the boys shot put class IX SMPN 1 Rokan koto IV. The population of this study was the son of a class IX student of SMPN 1 koto Rokan IV. In this research, there are class population. Samples of this study is not complete, or do not cover the entire study population, but only part of the population that was it. The researchers took a sampling technique focuses on purposive sampling technique. For the research data used to test the flexibility of the wrist arc, two hands-Ball Put Medicine and refusing to explosive bullets shot put. Data were analyzed with single product moment correlation. Based on the analysis of correlation data for rhitung X1 with Y = 0,423˃rtabel = 0.355 and X2 with Y to rhitung = 0,502˃rtabel = 0.355, while the X1 and X2 with Y = rhitung 0,521˃rtabel = 0.355. Because all the relationships shown in data analysis is significant, so it is Ha Ho accepted and rejected. This means there is a wrist flexibility and explosive power regarding the results of the boys shot put class IX SMPN 1 Rokan IV Koto. Where the provisions of correlation of a correlation of a variable with another set of variables rhitung˃ rtabel.Keywords: flexibility Wrists And Explosive Power, Shot Put